2020
DOI: 10.1093/hmg/ddaa026
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer risk SNP rs10993994 is a trans-eQTL for SNHG11 mediated through MSMB

Abstract: How genome-wide association studies-identified single-nucleotide polymorphisms (SNPs) affect remote genes remains unknown. Expression quantitative trait locus (eQTL) association meta-analysis on 496 prostate tumor and 602 normal prostate samples with 117 SNPs revealed novel cis-eQTLs and trans-eQTLs. Mediation testing and colocalization analysis demonstrate that MSMB is a cis-acting mediator for SNHG11 (P < 0.01). Removing rs10993994 in LNCaP cell lines by CRISPR/Cas9 editing shows that the C-allele cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Hence, in the present study the aim was to explore the detailed mechanism by which lncRNAs regulate TNBC proliferation and migration. Previously, it has been revealed that small nucleolar RNA host gene 11 (SNHG11) acted as a tumor promoter in lung ( 15 ), prostate ( 16 ) and liver cancer ( 17 ), but it has not been studied in TNBC. Therefore, the present study mainly investigated the role and regulatory mode of SNHG11 in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the present study the aim was to explore the detailed mechanism by which lncRNAs regulate TNBC proliferation and migration. Previously, it has been revealed that small nucleolar RNA host gene 11 (SNHG11) acted as a tumor promoter in lung ( 15 ), prostate ( 16 ) and liver cancer ( 17 ), but it has not been studied in TNBC. Therefore, the present study mainly investigated the role and regulatory mode of SNHG11 in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…For cis ‐eQTL analysis, we performed a meta‐analysis of our own linked genotype/gene expression data from prostate tissue with two data sets from dbGAP: a cohort of 470 prostate samples from dbGaP (phs000985.v1.p1) 27 and 752 samples from the Genotype‐Tissue Expression Project (GTEx) (phs000424.v7.p2) 28 . Details of our meta‐analysis approach are described elsewhere 29 . For each SNP, cis‐genes within 10 6 base pairs were taken for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…28 Details of our metaanalysis approach are described elsewhere. 29 For each SNP, cisgenes within 10 6 base pairs were taken for analysis. Each SNP was showed a significant (p < 1 × 10 −4 ) interaction term between SNP and age when regressed against log PSA, and were chosen to test in the validation cohort ( Figure 2).…”
Section: Cis-eqtl Meta-analysismentioning
confidence: 99%
“…The rationale underlies eQTL is that germline variations alter the transcription abundances of mRNA or other transcripts to cause phenotypic changes in the cell. Many studies demonstrated that eQTL can further affect a wider spectrum of transcripts by targeting at genes with trans ‐acting regulatory activities 5,6 . Several large data consortia have been established by eQTL mapping based on large parallel sequencing projects.…”
Section: Introductionmentioning
confidence: 99%